Ethical agency within the responsible tourism experience: a PARTicipative inquiry - Ingram, Claire (2018)
This thesis examines consumers’ ethical agency within the responsible tourism experience. It aligns with a post-structuralist, (late) Foucauldian position, adopting the theoretical constructs of ‘power struggles’ (1982), ‘problematisations’ (1984a) and ‘self-care practices’ (1984c) to engender a more fluid view of the market-consumer interface. It investigates (i) how consumers conform to, critique or resist market-promulgated ways of being a ‘responsible tourist’; (ii) how consumers (re)negotiate alternative meanings of how to be ethical and act ethically; (iii) what this reveals about the ways in which consumers retain, apportion or relinquish a sense of autonomy over their ethicality; and (iv) the tensions, struggles and dilemmas that consumers concurrently face.